Kiai's leadership in realizing independence Through the motivation and communication process (case study in Pesantren At Tanwir) - Winoto, Suhadi; Arifin, Miftah; Putra, Dhian Wahana (AMCA Journal of Religion and Society, 2022)
This study aims to describe and analyze the motivation and communication patterns of the santri (students of an Islamic boarding house or pesantren) to the Kiai (the leader of a pesantren, a kiai is also a religious leader in society) and the community in realizing the pesantren’s independence in Pesantren Kopi At-Tanwir. This research employs a qualitative approach with a case study design. This research reveals some points; first, the motivational patterns developed by the Kiai are: immersing confidence and belief in students and the community, engrossing an entrepreneurial spirit verbally by exemplary, and friendship with all stakeholders, both the community and government officials. Second, the communication patterns developed by the Kiai are direct or verbal communication, open communication, and communication through symbols.